ROLE AMBIGUITY AND ROLE CONFLICT ON ORGANIZATIONAL PERFORMANCE IN TELECOMMUNICATION SECTOR: TAKING JOB SATISFACTION AS A MEDIATOR - Aasim Naimat Gill; Muhammad Awais Ilyas; Raheel Amir Awan; Mohsin Raza (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
This paper investigates the role of ambiguity and conflict on organizational performance. Its very important to identify how these factors impact on organizational performance on such a sector where results or outcomes are very important. In this study the industry that was taken is telecommunication industry. Out of 410 questionnaires 228 were received and 186 were found usable. Convenience sampling, non-probability sampling technique was used. PLS-SEM software was used in the data analysis. The study therefore arranges and settles the significance of organizational performance to the organization that as long as the organizational employees take organizational performance seriously and should not let any odd or negativity impact their performance otherwise it will impact the performance of the organization. The more employees concentrate and work hard neglecting the odds in the organization, the more organizational performance will be rendered.